2022
DOI: 10.1037/sgd0000474
|View full text |Cite
|
Sign up to set email alerts
|

LGBTQ individuals’ lived experiences of hypervigilance.

Abstract: Lesbian, gay, bisexual, transgender, and queer (LGBTQ) individuals are at risk for poorer health outcomes in part because of stigma, discrimination, victimization, and resulting trauma and stress. Stigmarelated stress can lead to hypervigilance, or a chronic and pervasive state of alertness and readiness to respond to potential threats in the environment. The current study is one of the first to explore LGBTQidentified individuals' lived experiences of hypervigilance. In a brief online format, participants (N … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
28
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 49 publications
5
28
1
Order By: Relevance
“…The term hypervigilance has been used in past studies of LGBTQ-identified individuals; however, more attention is needed to define and operationalize the term as it applies specifically to LGBTQ-identified individuals. The current study suggests a factor structure and measure of hypervigilance in LGBTQ-identified individuals consistent with previous qualitative findings (Rostosky et al, 2021) and the conceptual dimensions of studies of hypervigilance in non-LGBTQ samples. The findings of the present study expand our understanding of the domains of hypervigilance experienced by LGBTQ-identified individuals and their relative associations with psychological health outcomes.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The term hypervigilance has been used in past studies of LGBTQ-identified individuals; however, more attention is needed to define and operationalize the term as it applies specifically to LGBTQ-identified individuals. The current study suggests a factor structure and measure of hypervigilance in LGBTQ-identified individuals consistent with previous qualitative findings (Rostosky et al, 2021) and the conceptual dimensions of studies of hypervigilance in non-LGBTQ samples. The findings of the present study expand our understanding of the domains of hypervigilance experienced by LGBTQ-identified individuals and their relative associations with psychological health outcomes.…”
Section: Discussionsupporting
confidence: 89%
“…We followed steps recommended by Boateng et al (2018) for scale construction and planned analyses. Item statements were created based on qualitative data provided by Rostosky et al (2021). The qualitative data were read for common statements associated with the themes of where (in what locations or settings) and around whom hypervigilance occurred, and the specific hypervigilant behaviors participants reported.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…1 We know that LGBT+ individuals may have encountered accumulative experiences of stigma and discrimination across their lives, which can have a negative impact on their health and can even have some bearing on their life expectancy. 2 The fear of stigma and discrimination can also impact on LGBT+ people accessing timely healthcare. Furthermore, there are barriers in our healthcare systems that increase these health inequities.…”
Section: Monitoring Patients' Sexual Orientation and Gender Identity:...mentioning
confidence: 99%